Dermatological Drug Development - Maeda-Chubachi, Tomoko (Cambridge Scholars Publisher, 2020)
This book uniquely summarizes approaches to developing dermatological drugs in a regulated environment from the perspective of the pharmaceutical industry. It brings together the insights of skilled and experienced industry experts to reveal the complexities of dermatological drug development, covering topical, oral, and biologic drugs. This book fills an important gap, as there is currently no other textbook addressing dermatological drug development, explaining and illustrating why unique nonclinical and clinical studies are necessary and how they are typically designed and conducted. The dr.